Developing commercial-scale fresh sweetpotato root storage in tropical areas of sub-Saharan Africa - Stathers, T.; Otieno, B.; Kipkoech, B.; Rees, D.; Precoppe, M.; Muoki, Penina Ngusye; Low, Jan W. (Elsevier, 2025)
As food systems across sub-Saharan Africa transform and urbanise, demand for all-year-round supplies for the raw materials is increasing. This demand can be met through combinations of staggering crop production, purchasing from diverse geographical areas, and storing produce. Focusing on the increasing use of orange-fleshed sweetpotato root puree in vitamin-A-rich food products, we ran a series of storage trials in Kenya to investigate whether commercial-scale fresh orange-fleshed sweetpotato storage could provide a stable supply of roots for puree production. The trials studied storage of roots of two sweetpotato varieties (Kabode and Vita), using washed versus unwashed roots in wooden crates, and mains grid power versus off-grid solar-powered storerooms for four-months. Following curing at 30 °C, roots were stored at 20–23 °C, and quality assessed. After four months storage, 54–59 % (Kabode) and 63–83 % (Vita) of initial root weight remained suitable for processing into puree. However, weevil and sprouting problems occurred. Vita outperformed Kabode for most criteria. Neither root washing nor different storerooms had a consistent effect on root quality. Subsequent trials in a solar-powered store investigated if lower temperatures of ≤15 °C and 90 % rh, with pre-harvest dehaulming could reduce weevil development, sprouting and rotting in stored roots. While control of sprouting and weevil damage was achieved and dehaulming improved stored root quality, while washing reduced it, high incidence of rotting and root weight loss occurred. Increasing store ventilation did not reduce rotting. We conclude that further trials with well controlled storage environments are required to understand how raw root quality, dehaulming, harvesting and handling practices, curing conditions, air exchange, and packaging materials affect quality during fresh root storage.